Correlation analysis of sacrococcygeal pressure and operation time in patients undergoing general anesthesia in the supine position. Issue 7 (July 2021) - Lu, Xiuying; Yang, Qing; Zhu, Lin; Liu, Lu; Tang, Honghua; Deng, Jiaying; Lu, Xiulan
Objective: This prospective study was performed to explore the change in sacrococcygeal pressure during an operation under general anesthesia in the supine position and identify the correlation between pressure injury and body mass index. Methods: This study involved 99 patients who underwent general anesthesia. Sacrococcygeal pressure was measured and recorded at seven time points: before general anesthesia, 5 minutes after general anesthesia, and 1, 2, 3, 4, and 5 hours after the beginning of the operation. The pressure change at each time point was compared, and the factors affecting the pressure were analyzed. Results: The correlation analysis showed that the operation time was significantly and positively associated with the occurrence of pressure injury. Conclusion: Perioperative management should be strengthened to speed up the surgical process and shorten the operation time, which will help to reduce the occurrence of intraoperative pressure injury.